Reconstituting the genome of a young allopolyploid crop, Brassica napus, with its related species. Issue 6 (7th January 2019) - Hu, Dandan; Zhang, Wenshan; Zhang, Yikai; Chang, Shihao; Chen, Lunlin; Chen, Yingying; Shi, Yongdi; Shen, Jinxiong; Meng, Jinling; Zou, Jun
Summary: Brassica napus (A n A n C n C n ) is an important worldwide oilseed crop, but it is a young allotetraploid with a short evolutionary history and limited genetic diversity. To significantly broaden its genetic diversity and create a novel heterotic population for sustainable rapeseed breeding, this study reconstituted the genome of B. napus by replacing it with the subgenomes from 122 accessions of Brassica rapa (A r A r ) and 74 accessions of Brassica carinata (B c B c C c C c ) and developing a novel gene pool of B. napus through five rounds of extensive recurrent selection. When compared with traditional B. napus using SSR markers and high‐throughput SNP/Indel markers through genotyping by sequencing, the newly developed gene pool and its homozygous progenies exhibited a large genetic distance, rich allelic diversity, new alleles and exotic allelic introgression across all 19 AC chromosomes. In addition to the abundant genomic variation detected in the AC genome, we also detected considerable introgression from the eight chromosomes of the B genome. Extensive trait variation and some genetic improvements were present from the early recurrent selection to later generations. This novel gene pool produced equally rich phenotypic variation and should be valuable for rapeseed genetic improvement. By reconstituting the genome of B. napus by introducing subgenomic variation within and between the related species using intense selection and recombination, the whole genome could be substantially reorganized. These results serve as an example of the manipulation of the genome of a young allopolyploid and provide insights into its rapid genome evolution affected by interspecific and intraspecific crosses.